FASHION K-POP IDOL AS A REPRESENTATION OF SOUTH KOREAN POP CULTURE - Lutfiatul Muawanah Almaani; Indra Tjahyadi (JURNAL LITERASI, 2023)
This research analyze Representation of South Korean Pop Culture in Fashion K-Pop Idol. One of the trends in K-Pop idol is a fashion outfit and fashion brand. The purpose of this study is to describe the meaning and describe representation in fashion K-Pop idol. The scope of this study is cultural study by using semiotics in Charles Sanders Pierce theory. The limitation of this research in the picture, fashion, outfit, accessories and brand of K-Pop idol, which describe representation of south korean pop culture in fashion K-Pop idol. The theory on semiotics analysis is based on Charles Sander Pierce : sign –object-interpretant, or is called the triangle theory of meaning. The method of this research use of method analize a research design, data source, data collection method and data analysis method The result shows that Korean teenagers are considered to have their own uniqueness, which is different from the fashion styles that come from Western countries so that the uniqueness of Korean-style clothes is identical to the bright colors of clothes and can easily be combined with Asian body colors and skin., K-Pop idol fashion is indeed in great demand by many people, especially K-Popers, they even imitate all the styles that their idols wear from outfit to brands worn by their idol.